PREVALENCE OF CROSSBITE IN SCHOOL CHILDREN OF SUNDAR INDUSTRIAL STATE AND RAIWIND, LAHORE: AN EPIDEMIOLOGICAL STUDY - Rabia Tabassum; Nazish Amjad; Faiza Malik; Munazza Saleem (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Crossbite is a commonly occurring malocclusion. It may be anterior or posterior, and it may occur either unilaterally or bilaterally. This study determined the prevalence of crossbite in children of different schools of Sundar industrial state and Raiwind. METHODOLOGY: Nine hundred (428 male and 472 female) children of various schools of Raiwind and Sundar Industrial State, Lahore, were examined. Information regarding age, sex, and crossbite were noted. The recorded data were analyzed by using SPSS version 20. Frequency distribution was used for the descriptive analysis. Statistical level of significance using student’s t-test was p< 0.05. RESULTS: Out of 900 children, 117(13%) were noted to have at least one tooth in crossbite, which was more frequent in permanent (13.2%) than in mixed dentition (12.3%). The prevalence of crossbite was slightly greater in female subjects (16.1%) than in male subjects (9.1%). Crossbite was seen more frequently in the posterior (6.3%) than the anterior region (5.9%). Combined anterior and posterior crossbite was found in 7(0.8%) children. Unilateral crossbite on the left side was found to be more frequent (6.6%) than on the right side (4.6%), and the bilateral crossbite was found to be in 1.9% of children. Buccal crossbite was more prevalent (6.8%) than lingual crossbite (5.8%). Combined lingual and buccal crossbite was found to be in 0.4% of children. CONCLUSION: Crossbite is a frequently occurring malocclusion in school children of Sundar industrial state and Raiwind, Lahore. Posterior crossbite is more prevalent than anterior crossbite.